Pengaruh Growth Mindset Terhadap Employee Resilience di Unit Foods PT X - Patricia Aurellia; Debora Basaria; Reza Fahlevi (unprimdn.ac.id, 2024)
PT X is one of the companies engaged in Fast Moving Customer Goods (FMCG) in Indonesia, located in Jakarta. The achievement of PT X certainly must maintain the role of qualified employees so that the company can increase its productivity, efficiency, and competitiveness to excel in competition in the era of globalization. The intense competition in the FMCG industry encourages PT X's Foods unit employees to withstand pressure and rise from failure to continue to grow. To encourage employee performance, PT X applies several values to support the effectiveness of employee performance in achieving targets, one of which is a growth mindset. Some previous research results show ambiguity in the relationship between a growth mindset and employee resilience. Therefore, this study aims to determine the effect of a growth mindset on employee resilience in the PT X Foods unit. Research data were obtained through the distribution of Google Forms to 87 employees who met the criteria for research characteristics. The results of this study's data analysis indicate an effect of a growth mindset on employee resilience in the Foods unit of PT X with a Sig value. 0,000 < 0,05. In addition, the coefficient of determination shows that the effect of growth mindset on employee resilience is 15%, while other variables influence the remaining 85%.